Mendefinisikan Ulang Pluralisme Agama sebagai Sebuah Tantangan Global - Gunawan Adnan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2011)
This paper will try to answer some questions about religious pluralism. Does religious pluralism mean to receive the truth of all religions, as expressed by their founders, although of some religious doctrines are contradictory to each other? What kind of the religious pluralism concept that will be able to resolve the problems of conflict based on religion? Are there other options that can be applied in resolving these problems?Keywords: Religion, conflict, pluralism.DOI: 10.15408/ref.v13i1.992